Analisis kinerja petugas puskesmas Baumata dan Naibonat terhadap pencapaian standar pelayanan minimal kesehatan di kabupaten Kupang - Kikhau, Adriana M. O.; Littik, Serlie K. A.; Berek, Norce Ch.; Muntasir; Junias, Marylin S. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Performance is the level of achievement of the implementation of an activity, program, or policy within an organization. The SPM reports of Baumata and Naiboant Community Health Centers (Puskesmas) indicate that there was no significant improvement in the years 2020 and 2021. The achievement trend displayed fluctuation. The insignificant improvement is also reflected in several indicators showing a decline. This study aims to analyze the impact of the performance of Community Health Center staff on the achievement of Health Sector SPM in Kupang District. The method used in this research is quantitative research with a cross-sectional approach, with the population in this study being all staff of Baumata and Naibonat Community Health Centers, totaling 75 people. The sampling technique used in this study is saturated sampling, where all populations are used as samples. Data were analyzed using Multiple Logistic Regression test, indicating that work motivation, organizational support, and competence variables have a significant relationship with the performance of staff at Baumata and Naibonat Community Health Centers with sig. p values of 0.03, 0.01, and 0.000 (p < 0.05), respectively. Therefore, work motivation, organizational support, and staff competence need to be improved for better service in achieving the designated SPM targets.